2019
DOI: 10.1002/suco.201800302
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and durability properties of self‐compacting mortars containing binary and ternary mixes of fly ash and silica fume

Abstract: In this paper, the results of experimental work on the strength and durability performances of self‐compacting mortars (SCMs) manufactured from silica fume (SF) and fly ash (FA) were presented. The cement was partially replaced with 5, 10, 15, 20, and 25% of FA and 5, 10, and 15% of SF as binary mixes. Also, ternary mixtures were prepared by the incorporation of FA and SF at different replacement dosages by weight. In total, 14 different combinations of mixes were studied at the ages of 7, 28, and 180 days. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…These later showed that the SCC has a better performance compared to the regular concrete . Benli has shown that the SCCs density decreases with the increase of silica fume content compared to the regular concrete. It was also shown that the mixtures made with silica fume have a poor performance in terms of workability compared to the mixtures made with others minerals type.…”
Section: Introductionmentioning
confidence: 94%
“…These later showed that the SCC has a better performance compared to the regular concrete . Benli has shown that the SCCs density decreases with the increase of silica fume content compared to the regular concrete. It was also shown that the mixtures made with silica fume have a poor performance in terms of workability compared to the mixtures made with others minerals type.…”
Section: Introductionmentioning
confidence: 94%
“…Self‐compacting concrete (SCC) is an extremely flowing concrete that compacts underneath its own weight and does not need any vibrators or external source of energy to fill the mold, narrow openings and cramped reinforcement . SCC has a viscosity such that it does not segregate and bleed .…”
Section: Introductionmentioning
confidence: 99%
“…Self‐compacting concrete (SCC) is an innovative concrete that has high flowability for filling the narrow spacings of reinforcement and corners of molds without any requirement of vibration and compaction . SCC can be placed under its own‐weight, and its cohesiveness is adequate to be processed without segregation or bleeding .…”
Section: Introductionmentioning
confidence: 99%